PENDAMPINGAN MASYARAKAT SADAR WISATA DALAM PEMBUKAAN PARAWISATA AIR TERJUN SARAMBU PATIRO URAN DAN SARAMBU KAMBUTU DI LEMBANG RANTEBUA KECAMATAN RANTEBUA - Yohanis Lotong Ta'dung; Randi Tangdialla; Ade Lisa Matasik; Mince Batara; Grace Sriati Mengga (Yayasan Education and Social Center, 2021)
Sarambu Patiro Uran waterfall and Sarambu Kambutu' waterfall in Rantebua are one of the prospective tourist destinations in North Toraja Regency. This waterfall has the potential to become a new tourist destination, but because of the lack of maximum management makes it abandoned. The purpose of this PKM is to develop Sarambu Patiro Uran and Sarambu Kambutu'to become one of the favorite natural tourist destinations in North Toraja Regency. The methods used are discussions, tutorials, and mentoring. The results of the activity were able to promote Sarambu Patiro Uran's tejuan Water and Sarambu Kambutu's social media. However, efforts to lift Sarambu Patiro Uran Waterfall and Sarambu Kambutu' into new tourist destinations are constrained by several things, including: (a) road access that is not good, (b) limited infrastructure facilities, (c) managerial systems that are not good, (d) lack of promotion, and (e) water discharge that drops when the drought is long